2008
DOI: 10.1166/jnn.2008.1219
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Biophysical Characterization of Pluronic F127-Dendrimer Conjugate as a Delivery Agent of Antisense Oligonucleotides

Abstract: A series of pluronic F127 conjugated PAMAM dendrimer generation 5 were prepared to evaluate the potential use of dendrimer-pluronic conjugates as a delivery agent of antisense oligonucleotides. The structural features of the conjugates were identified by FT-IR and 1H-NMR spectra. The prepared dendrimer generation 5-pluronic F127 conjugates showed particle size in the range of 50 to 130 nm with reduced zeta potential. The electrophoretic property of conjugates was further confirmed by capillary zone electrophor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…The presence of these terminal groups in dendrimers facilitates multiple simultaneous interactions with other molecules 2. As one of the most popular dendrimers, generation 5 (G5) PAMAM dendrimers with 128 amine terminals have been successfully used in field of biomedicine such as drug delivery, gene transfection, imaging, and anti‐infection 3–15…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of these terminal groups in dendrimers facilitates multiple simultaneous interactions with other molecules 2. As one of the most popular dendrimers, generation 5 (G5) PAMAM dendrimers with 128 amine terminals have been successfully used in field of biomedicine such as drug delivery, gene transfection, imaging, and anti‐infection 3–15…”
Section: Introductionmentioning
confidence: 99%
“…2 As one of the most popular dendrimers, generation 5 (G5) PAMAM dendrimers with 128 amine terminals have been successfully used in field of biomedicine such as drug delivery, gene transfection, imaging, and anti-infection. [3][4][5][6][7][8][9][10][11][12][13][14][15] Despite the extensive interest in pharmaceutical applications of dendrimers, there are conflicting reports regarding their biological safety. 16,17 It has been reported that G2-G4 PAMAM dendrimers would cause concentration-and generation-dependent damage to red blood cells (RBCs).…”
Section: Introductionmentioning
confidence: 99%
“…These drugs also affect proteins or nucleic acids that are present in normal as well as malignant tissues. Targeted therapy (23,24) using pluronic F68 as a carrier may be more effective than current treatments and less harmful to normal cells. Pluronic F68 appears to possess unique drug-targeted cancer cell interactions in the K5262 cell line.…”
Section: Discussionmentioning
confidence: 99%
“…Among of the copolymers, pluronic F127 and its derivatives have been the most widely studied materials for delivering several kinds of drugs and proven its loading efficiency [2,3,29,31,32]. Pluronic F127 was also used to functionalize PAMAM dendrimers.…”
Section: Introductionmentioning
confidence: 99%